Land in Limbo: Understanding path dependencies at the intersection of the port and city of Naples - De Martino, Paolo (A+BE | Architecture and the Built Environment, 2021)
Ports and cities form an articulated and interconnected territory where a multitude of actors–with contrasting motivations and responsibilities–shape decisions across different scales. For each of these actors the concept of port-city relationship has a specific meaning and spatial quality. Today, in many European port cities national port reforms are promoting integration between ports and inland corridors, leading to port merging within the same regional territory. In Italy, starting in 2016, this has allowed for the creation of systems between ports belonging to the same regional territory. On the one hand, this cooperation between ports offer enormous opportunities to reformulate the port-city relationship from a different scale. On the other hand, this collide with a plurality of actors–municipalities and port authorities among others– who have historically planned ports and cities as autonomous entities, thus strengthening specific ideologies and governance mechanisms. A change of perspective would require new spatial configurations. In particular, this thesis focuses on the role that history has played in the definition of the relationship between port and city in Naples and in particular on what historical institutionalists have defined as “path dependence”. Path dependence suggests that each action lies within an articulated system of decisions previously undertaken. This dependence is based on a self-reinforcing principle and it translates into rigid and inertial planning models that have looked, in particular in the case of Naples, at port and city as separate elements in a limbo between the need for renewal and resistance to change. This condition, several times in the thesis described as a waiting condition, has become historicized, making it difficult for the different actors to identify alternative approaches. Path dependence therefore is an interpretative tool of particular interest for the analysis of port cities. Port cities are landscapes in transition, places at the intersection of land and water where two different cultural and planning approaches coexist and collide: the port and city ones. Here, the collaboration between the port authority, the municipality, the state and the regions has generated separation and sectoriality. The dependencies today affects different scales (local, regional and landscape) and dimensions (cultural, economic, environmental). Consequently, this thesis investigates how path dependence can become a knowledge tool for the port territory of Naples, to understand and interpret its spaces, institutions and mechanisms that have generated separation in order to better understand whether to introduce new and possible forms of integration. To answer the question, the thesis carried out a spatial-institutional analysis arguing that spatial transformations in port cities can be better understood as a result of a complex decision-making system and therefore strongly linked to governance models. Rotterdam, Antwerp and Le Havre have been selected and analyzed as embematic cases to give concrete answers to the dependencies emerged in Naples. Mapping these port city territories, their spatial and governance structures and how these have evolved over time, is used as a cognitive and methodological tool and to highlight, as in the case of Naples, a mismatch between the spatial ambitions of the various actors and how on the contrary, the territory has evolved over time. Historical archive research, policy documents analysis and interviews to the most relevant actors in Naples and over Europe shape the methodological approach. The PhD research aims to provide new insights on the history of the port city of Naples and its evolutionary process in relation to path dependencies. Furthermore, by analyzing the challenges and opportunities that other port and city authorities all over Europe are facing today, the research aims to establish an abacus of possible solutions useful to inspire the Port Network Authority of the Central Tyrrhenian Sea which, since 2016, represents the new government agency in charge of the Campania port territory. The study concludes by pointing out the urgency in Naples to identify new spatial configurations aimed at integration, new collaborations at the scale of the city and the region and, fundamentally, a profound shift in the governance structure and mindset of the authorities as well as an update of the planning tools, which are still based today on an idea of dividing the territory into fragments rather than on the will to integrate them. The research therefore has the ambition to provide a different perspective, which looks at the porosity of the territory, useful for helping the various authorities to plan, albeit in the context of different interests, a more sustainable relationship between port and city.